Gaya Bahasa dan Fungsi Iklan pada Majalah LifeWear Uniqlo : Language Style and Function of Advertisements in Uniqlo's LifeWear Magazine - Sultan Maulana Malik Zidan; Umul Khasanah (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2023)
Abstract. The purpose of this study was to analyze the linguistic styles found in the three clothing categories of LifeWear Magazine Uniqlo Edition 08 Spring & Summer 2023: 'wardrobe essentials', 'art of everyday life' and 'Melbourne magic'. . This is a method of descriptive analysis using reading and note-taking methods for the language style data published in LifeWear Magazine Uniqlo Edition 08 Spring & Summer 2023 "The Art of Everyday Life". The analysis found that the magazine's three clothing categories use five different linguistic styles: anthropomorphic, metaphorical, simile, hyperbole, and antithesis. Each clothing category has a different variation of speaking. The Wardrobe Essentials category has 4 personifications, 1 simile, 2 hyperbole, and 1 antithesis. The "everyday art" category has 1 anthropomorphism, 1 exaggeration, and 1 metaphor. There are currently 2 personifications, 2 metaphors, and 1 fable in the Melbourne Magic category. Keywords: Language Style, Magazine, Uniqlo. Abstrak. Tujuan dari penelitian ini adalah menganalisis gaya bahasa yang terdapat di dalam tiga kategori pakaian Majalah LifeWear Uniqlo Edisi 08 Spring & Summer 2023 "The Art of Everyday Life" yaitu Wardrobe Essentials, The Art of Everyday Life, dan Melbourne Magic. Metode yang digunakan adalah analisis deskriptif terhadap data yang berupa gaya bahasa dalam Majalah LifeWear Uniqlo Edisi 08 Spring & Summer 2023 "The Art of Everyday Life" dengan menggunakan teknik baca dan catat. Hasil analisis menunjukkan bahwa terdapat lima jenis gaya bahasa yang digunakan dalam tiga kategori pakaian dalam majalah, yaitu Personifikasi, Metafora, Simile, Hiperbola, dan Antitesis. Setiap kategori pakaian memiliki variasi penggunaan gaya bahasa yang berbeda. Pada kategori Wardrobe Essentials, terdapat 4 Personifikasi, 1 Simile, 2 Hiperbola, dan 1 Antitesis. Pada kategori The Art of Everyday Life, terdapat 1 Personifikasi, 1 Hiperbola, dan 1 Metafora. Sedangkan pada kategori Melbourne Magic, terdapat 2 Personifikasi, 2 Metafora, dan 1 Simile. Kata Kunci: Gaya Bahasa, Majalah, Uniqlo.